(untitled) (Revista LIDER, 2020)
Initially the scientific analysis of the landscape gets highlighted with the studies of Paul Vidal de La Blache, belonging to the French school, which we will focus on the concept of region and landscape, and this is parsed through the description of genres of life. In the early 20th century with the study of Carl Ortwin Sauer, an exponent of the AngloSaxon school, the descriptive practice of landscape is replaced by an interpretative one, seeking to understand the ways in which people leave their mark on the landscape, analyzing their production activities and their settlements. From the late 1970 analysis of landscape is invigorated by the emergence of New Cultural Geography, passing through the imaginary, i.e. the non-material, covering topics such as perception, representation, experience, geosymbols, however, without neglecting its material aspect. The analysis of the cultural landscape gains strength with an increase of the contribution of ethnomethodologies, providing intelligibility about perceptions and representations of human groups in relation to the landscape, allowing one to understand how people think and act about the landscape that permeates and hosts them, and which is perceived, practiced and experienced. Thus, the present text aims to show the various connotations of the concept of landscape, trying to emphasize the importance of the study of the cultural landscape in a rural environment, and how ethnomethodologies can collaborate for such analysis.